Dream City : Ein Münchner Gemeinschaftsprojekt. - Kunstverein München; Museum Villa Stuck, München; Siemens Kulturprogramm, München; Autorenkollektiv des Geographischen Instituts der Technischen Universität München = Authors from the Geographical Institute of the Technical University of Munich; Bardot, Brigitte; Beuys, Joseph; Birnie Danzker, Jo-Anne; Bronson, AA; Clegg & Guttmann; Craig, Stephen; Feldmann, Hans-Peter; Friedl, Peter; et al. (München : Kunstraum München, 1999)
Acconci, Vito ; Beuys, Joseph ; Feldmann, Hans-Peter ; Metzger, Gustav ; Rosler, Martha ; Bronson, AA ; Erkmen, Ayse ; Gonzalez-Torres, Felix ; Hohenbüchler, Christine & Irene ; Karamustafa, Gülsün ; Metzel, Olaf ; Rollins, Tim & K.O.S. ; Schütte, Thomas ; Stumpf, Manfred & Annette ; Craig, Stephen ; Kern, Stefan ; Peterman, Dan ; Rostásy, Andrea ; Ackermann, Franz ; Clegg & Guttmann ; Heger, Swetlana ; Dejanov, Plamen ; Doderer, Yvonne P. ; Friedl, Peter ; Knorr, Daniel ; Lanzinger, Pia ; Melián, Michaela ; Römer, Stefan
biog., ind. tent., gr. tent., bibliog. per kunstenaar
Duits & Engels
Dream City : Ein Münchner Gemeinschaftsprojekt, Kunstraum München ; Kunstverein München ; Museum Villa Stuck, München ; Siemens Kulturprogramm, 25. März bis 20. Juni 1999
boek
Keywords: München